2017
DOI: 10.2138/am-2017-6015ccby
|View full text |Cite
|
Sign up to set email alerts
|

Continuous mush disaggregation during the long-lasting Laki fissure eruption, Iceland

Abstract: Plagioclase textures were investigated in the products of the voluminous 1783-1784 CE Laki eruption from the Eastern Volcanic Zone (EVZ) of Iceland to establish whether mush disaggregation occurred solely at the onset of the eight-month eruption or throughout its whole duration. Phase proportions and plagioclase size distributions were determined using standard optical and manual techniques as well as automated approaches based on Quantitative Evaluation of Minerals by SCANing electron microscopy (QEMSCAN). Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 58 publications
(119 reference statements)
0
17
0
Order By: Relevance
“…4d') could result from either the heterogeneous nucleation of the droplet on the surface of a pre-existing pillar, or formation of the pillar by growth from a Fe-rich liquid after heterogeneous nucleation of the droplet on an originally planar plagioclase crystal face. If the former, then we might expect pillars to be a commonly observed feature of rapidly cooled basalts in which diffusion-limited growth occurs, but they are not (Helz and Wright 1992;Neave et al 2017). Consequently, following Philpotts (1981), we suggest that pillar formation post-dates the attachment of the Fe-rich droplets, and that the presence of a Fe-rich droplet destabilizes the plagioclase planar growth face, resulting in localised enhanced growth of plagioclase.…”
Section: Plagioclase Pillarsmentioning
confidence: 76%
“…4d') could result from either the heterogeneous nucleation of the droplet on the surface of a pre-existing pillar, or formation of the pillar by growth from a Fe-rich liquid after heterogeneous nucleation of the droplet on an originally planar plagioclase crystal face. If the former, then we might expect pillars to be a commonly observed feature of rapidly cooled basalts in which diffusion-limited growth occurs, but they are not (Helz and Wright 1992;Neave et al 2017). Consequently, following Philpotts (1981), we suggest that pillar formation post-dates the attachment of the Fe-rich droplets, and that the presence of a Fe-rich droplet destabilizes the plagioclase planar growth face, resulting in localised enhanced growth of plagioclase.…”
Section: Plagioclase Pillarsmentioning
confidence: 76%
“…A widespread view is that these macrocrystals crystallised at middle to deep crustal levels and accumulated in a crystal mush layer from which they were picked up by their host/carrier melt during ascent. Well documented examples of Icelandic Holocene lavas, where prior studies have demonstrated the importance of such a magma mush layer, include the 8600 BP Þjórsárhraun lava 3 , the 1783 Laki lava 6,63 , and more recently the 2014-15 Holuhraun lava 7,35 . Consideration of elemental diffusion in these crystals and their melt inclusions demonstrates that timescales associated with the crystal entrainment process are likely to be short, or equivalent to timescales of these eruptions, i.e., a few weeks to months 3,7,64 .…”
Section: Methodsmentioning
confidence: 99%
“…In line with these observations, we suggest that an important process for formation of sustained magma channels is the addition of mush crystals to a magmatic liquid as it leaves a magma body and rises towards the surface. In this case, a near-continuous addition of mush crystals into the host/carrier melt 63 , in proportion to the rate of magma flow, leads to uniform crystal content throughout the erupted magma, despite variable rate of flow. We suggest that erosion of such a crystal mush layer may ultimately lead to formation of sustained openings, which are required for the extraction of a melt from a magma body.…”
Section: Methodsmentioning
confidence: 99%
“…Overwhelming documentation of the prevalence of antecrysts in magmatic systems (e.g., Bacon and Lowenstern, 2005;Humphreys et al, 2006;Smith et al, 2009;Viccaro et al, 2010;Neave et al, 2013Neave et al, , 2014Neave et al, , 2017van der Zwan et al, 2013;Witter et al, 2016) has been critical for the development of mushdominated paradigms of magmatic systems (e.g., Edmonds et al, 2019;Sparks et al, 2019). Entrained crystals can be identified by major element and/or isotopic compositions that are not in equilibrium with the transporting magma (e.g., Morgan et al, , 2007Berlo et al, 2007;Martin et al, 2010;Sakyi et al, 2012;Cashman and Blundy, 2013;Sides et al, 2014;Brenna et al, 2018;Shane et al, 2019) and by evidence of deformation in crystalrich mush zones (e.g., Kahl W. et al, 2017;Befus et al, 2019;Holness et al, 2019;Wieser et al, 2020).…”
Section: Complex Crystallization In Volcanic Systemsmentioning
confidence: 99%
“…Here I suggest an additional approach that complements the applications of isotope tagging and diffusion chronometry described above. When crystal cores and rims/groundmass differ in composition, the contribution of different crystal components to the overall sample crystallinity can be assessed using compositional maps made directly from BSE images or element maps (e.g., Muir et al, 2012), including automated analysis such as QEMSCAN (e.g., Neave et al, 2014Neave et al, , 2017. To illustrate the use of compositional information in BSE images, I use an example from Mount St. Helens, where the diversity of the plagioclase population has been well documented (e.g., Berlo et al, 2007;Cashman and Blundy, 2013).…”
Section: Alternative Approaches To Csd Analysis Of Complex Crystal Pomentioning
confidence: 99%